2021
DOI: 10.1016/j.radi.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Radiographers’ perception on task shifting to nurses and assistant nurses within the radiography profession

Abstract: Introduction:The radiography profession is challenged by greater responsibilities and shortage of educated radiographers. Implementation of task shifting is one strategy to deal with the current situation in health care. The aim of this studiy was to evaluate radiographers' perception of assistant nurses and nurses carrying out tasks that traditionally were undertaken within the radiography profession in a Swedish context. Methods: An electronic questionnaire was distributed to radiographers at eleven hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nurses were found to have statistically higher practice scores than radiographers. This could be due to IPC training differences between radiographers and nurses, but also due to the greater care-focused role that radiology nurses play while radiographers focus on technical related imaging tasks [ 19 ]. A study in Sweden assessed surface contamination in CT and found no or minimal bacterial cultures on cannulation trolleys which are commonly maintained by nurses, however, that same study found bacteria in the CT control rooms, which typically are not required to be as heavily cleaned as cannulation trolleys and may highlight poor hand hygiene practices by radiographers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses were found to have statistically higher practice scores than radiographers. This could be due to IPC training differences between radiographers and nurses, but also due to the greater care-focused role that radiology nurses play while radiographers focus on technical related imaging tasks [ 19 ]. A study in Sweden assessed surface contamination in CT and found no or minimal bacterial cultures on cannulation trolleys which are commonly maintained by nurses, however, that same study found bacteria in the CT control rooms, which typically are not required to be as heavily cleaned as cannulation trolleys and may highlight poor hand hygiene practices by radiographers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%